Ethnobotanical study of medicinal plants used for Wound healing in North Waziristan, Pakistan - Rehman, Sabith; Iqbal , Zafar; Qureshi, Rahmatullah; Younas, Muhammad; Ur Rahman, Khursheed; Hussain, Wahid; W. Bussmann, Rainer (Ethnobotany Research and Applications, 2025)
Background: Pakistani communities possess a rich tradition of healthcare knowledge, particularly in the use of medicinal plants. The local community of North Waziristan similarly relies on a wide variety of plant species for treating burns, cuts, and wounds. This region is especially significant due to its rich biodiversity, well-preserved indigenous knowledge systems, limited access to modern medical facilities, and a strong cultural dependence on traditional remedies. Therefore, this survey aims to document and explore the therapeutic use of medicinal plants for wound healing in this relatively under-researched region of Pakistan. Methods: Ethnomedicinal knowledge was collected through face-to-face, semi-structured interviews with approximately 130 local informants from the research area, representing diverse educational backgrounds and socioeconomic statuses. In addition sixty-one questionnaire-based interviews were conducted in selected villages. Various ethnobotanical indices, such as Use value (UV), Relative frequency of citation (RFC), and Fidelity level (FL), were used to analyze the data. Results: A sum of 69 plants, relating to 45 families, was reported for their use in healing 18 different wound-related ailments. Asteraceae was the leading plant family with 8 plant species, followed by Solanaceae with 4 plant species. The most frequently used growth forms were Herbs (59.42%), followed by shrubs (20.29%). Leaves (40.96%) were the heavily utilized plant part used in herbal medication, and paste (32.43%) was the most frequent herbal preparation method. Among the most frequently cited species were Bergenia ciliata (0.87), followed by Agave cantala and Salvia macrosiphon (0.84 each), Ephedra procera (0.82), Berberis lycium (0.81). Conclusions: These medicinal plants, which are used to heal wounds, are facing severe threats and therefore need to be conserved. Documenting traditional knowledge not only aids in preserving cultural heritage but also offers a valuable starting point for bioactive compound discovery, potentially leading to the development of novel wound-healing agents in modern medicine. Advanced research should focus on the implementation of phytochemical and pharmacological activity in these valuable herbal drugs. Keywords: Ethnomedicine wound healing, herbal remedies, traditional knowledge, North Waziristan, Pakistan.